Pelibatan Keluarga dalam Program Sekolah untuk Menanamkan Kedisplinan Anak Usia Dini - Rusuli, Izzatur; Damayanti, Safrina (Lembaga Swadaya Masyarakat Asosiasi Masyarakat Madani Indonesia (AMMI), 2023)
Discipline internalization in schools cannot be achieved successfully if it is not accompanied by family involvement. This study aims to determine the attitude toward discipline instilled and to find out the programs held by the school involving families and the factors that influence the implementation of family involvement in disciplining children. This study uses a qualitative descriptive approach with data collection techniques in the form of observation, interviews, and documentation. Data sources in this study were principals, class teachers, and parents in AL-Hikmah Integrated Islamic Kindergarten's children. The results showed that the discipline that emerged in children was being on time, obeying the rules, putting things in their place, and doing self-cleaning. Meanwhile, family involvement programs are held in the form of meetings in the first academic year, parenting, intensive communication, and assistance on field trip activities. Factors that support family involvement in school programs are due to the awareness and concern of parents for their child's development. Meanwhile the inhibiting factor is the busyness of parents.